Self-reported, self-care activities among type 2 diabetic patients in rural areas of Kancheepuram district, Tamil Nadu: a cross-sectional study - Kalusivalingam, N.; Bobhate, Prateek; Kalaivani, A.; Karnaboopathy, R. (International Journal Of Community Medicine And Public Health, 2020)
Background: Diabetes is a chronic condition. The burden of diabetes is, expected to rise to 592 million by 2035. Diabetes self-care activities can have a dramatic impact on lowering glycosylated hemoglobin levels. Hence, this study has been planned to assess the self-care activities among the type 2 diabetes patients in rural areas of Kancheepuram district, Tamil Nadu. Methods: A cross-sectional study was conducted among type 2 diabetic patients residing in rural field practice area of Shri Sathya Sai Medical College and Research Institute, Kancheepuram district during May 2019 and June 2019. Personal interview using semi-structured questionnaire including summary of diabetes self-care activities- revised version was conducted. Results: Majority of the study participants were female and 46.2% were above 51 years of age. Majority had diabetes mellitus for 1-5 years. Of the diabetic self-care activities 68.5% had healthy eating 2-4 times/week. About 33.2% of the participants were not indulged in physical activity as well as high-intensity exercises even for a single day; about 33% had not tested their blood sugar level for even a single time and only 1.5% had checked their feet on all days during the previous week. Higher food scores were found significantly associated with availability of family support for self-care activities (p value 0.020). Conclusions: Of the diabetic self-care activities the healthy dietary component was followed satisfactorily but exercise, foot care and testing of blood sugar were followed poorly by the study participants.